Penerapan Picture Word Inductive Model (PWIM) untuk meningkatkan keterampilan menulis kalimat efektif peserta didik kelas IVB di SD Al-Islam 3 Gebang, Surakarta. - Annida Rahma Aulia; Jenny Indrastoeti Siti Poerwanti (Universitas Sebelas Maret, 2025)
This study aims to describe the application of the Picture Word Inductive Model (PWIM) in improving the effective sentence writing skills and improving the effective sentence writing skills of grade IVB students at SD Al-Islam 03 Gebang, Surakarta 2024/2025 learning year through the application of the learning model. This research is a type of Classroom Action Research (PTK). The findings of this study are: Picture Word Inductive Model (PWIM) with 6 syntax, namely, studying photos and digging words, analysing the properties of words and forming categories, creating sentences, creating titles, classifying sentences, and writing from sentences to paragraphs are well applied in Indonesian language learning to improve the effective sentence writing skills. The effective sentence writing skills of grade IVB students of SD Al-Islam 03 Gebang, Surakarta have improved after learning with the Picture Word Inductive Model (PWIM) which is shown by an increase in the original average of 59 in pre-action to 70 in cycle 1 and continues to increase to 86 in cycle 2 and an increase in classical completeness from 22% to 43% in cycle 1 and 87% in cycle 2